2012
DOI: 10.1140/epjd/e2012-20739-7
|View full text |Cite
|
Sign up to set email alerts
|

Instability control in microwave-frequency microplasma

Abstract: Abstract. Atmospheric argon microplasmas driven by 1.0 GHz power were studied by microwave circuit analyses and spatially-resolved optical diagnostics. These studies illuminate the mechanisms responsible for microplasma stability. A split-ring resonator (SRR) microplasma source is demonstrated to reflect excess microwave power, preventing the ionization overheating instability while limiting electron density to approximately 1 × 10 14 cm −3 and OH rotational temperature to 760 K at 0.76 W. Providing the SRR mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Peak values are on the order of a few times 10 20 m À3 , in line with several previous measurements. 14,15,22 The widths of the microplasma filaments also increase with frequency and are on the order of 400 lm, comparable to the electrode sizes.…”
Section: Example Datamentioning
confidence: 79%
See 1 more Smart Citation
“…Peak values are on the order of a few times 10 20 m À3 , in line with several previous measurements. 14,15,22 The widths of the microplasma filaments also increase with frequency and are on the order of 400 lm, comparable to the electrode sizes.…”
Section: Example Datamentioning
confidence: 79%
“…Net power is reported as calibrated forward minus reflected power after correction for cable loss. 15 Losses on the microstrip itself are not included in this correction. Due to the short 1 cm length, however, these are estimated from the material manufacturer's specifications to be less than about 2% of the power at all examined frequencies, well within the measurement uncertainty.…”
Section: B Electrical and Spectroscopic Diagnosticsmentioning
confidence: 99%
“…For transmission line microplasmas, where the transmission line has an impedance of 50 Ω, the electron density must be on the order of 10 15 cm −3 in a matched circuit, a value which was confirmed by electron density measurements based on the Stark broadening of the H β line emission at 486.1 nm [87]. For microwave discharges generated in a resonator circuit [12], the electron density is limited to approximately 10 14 cm −3 for optimum power coupling, a value which was confirmed by measurements in a split-ring resonator microplasma, again using Stark broadening of the of the H β line [87].…”
Section: Electron Densitymentioning
confidence: 83%
“…During the last decade, the microdischarges for a wide range of interelectrode gaps were extensively studied both experimentally and theoretically (see, for instance, [1][2][3][4][5][6][7][8] and references therein). It was found that for gaps <10 µm the dominant electron emission mechanism is the field emission (FE), while for larger gaps it is the secondary electron emission (SEE) due to the ion bombardment.…”
Section: Introductionmentioning
confidence: 99%
“…Microplasma can be subjected to a variety of instability mechanisms. For example, microwave (1 GHz) sustained microplasmas with interelectrode gap sizes of ∼100 µm are subject to the ionisation overheating instability (IOI) [7, 8]. In brief, IOI results from electron collisional heating of the gas, which leads to a decrease in the background density and an increase in the reduced electric field ( E / N g ) [9].…”
Section: Introductionmentioning
confidence: 99%